Incidence of Rose Bengal Positive Agglutination Test Among Blood Donors in Sulaimani Blood Bank17-24 - Omer, Sherko A. (Sulaimani Journal for Pure and Applied Sciences, 2004)
This study was achieved to determine Brucella antibodies using Rose Bengal agglutination test in serum of healthy persons attending a blood bank in Sulaimani city in Iraqi Kurdistan region, each person's serum was tested directly without dilution and with 1:80 dilution, the overall positive agglutination results were observed in 29 out of 548 cases (5.29%). Twenty seven of them gave negative reaction with 1:80 dilution, we recommend that if only Rose Bengal test is used to confirm diagnosis of brucellosis, titration of patients serum is useful for better evaluation.
Keywords: Brucellosis; Agglutination; Rose Bengal test; blood donors